IMPLEMENTASI KEBIJAKAN PEMBERIAN TPP DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA PROBOLINGGO - Puspitasari, Ekky; Endarti, Esa Wahyu; Kurniawan, Satunggale (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
This study aims to determine and analyze the mechanism for providing Additional Employee Income at the Probolinggo City Human Resources Development and Personnel Agency. The research method used is descriptive qualitative with an inductive approach. The research was conducted at the Probolinggo City Human Resources Development and Personnel Agency. Based on the results of the research and data processing, it can be concluded that the mechanism and implementation of the Employee Income Policy are running optimally and are in accordance with the Probolinggo Mayor Regulation Number 6 of 2024 concerning the Second Amendment to the Probolinggo Mayor Regulation Number 27 of 2022 and the Probolinggo Mayor Regulation Number 15 of 2023 concerning the Provision of Additional Employee Income. This policy is able to improve the performance, discipline, competence and welfare of ASN. There are several supporting factors in the implementation of the TPP Granting policy at BKPSDM, namely Resources (budget), attitudes and bureaucratic structures. The inhibiting factors include in terms of resources (facilities) server capacity which sometimes takes a long time to respond when used at the same time and resources (Human Resources) there are several employees who are constrained in inputting performance activities on the application, less friendly with the application due to age factors that are almost retired.